Design and limitations in polymer cracking fluidized beds for energy recovery - Antelava, Ana; Pallari, Elena; Manos, George; Constantinou, Achilleas (My University, 2019)
The rise in the manufacturing of plastics increases the waste streams generated. The most popular way to treat plastic that cannot be recycled is to use energy recovery methods or landfill the waste. As plastic is nonbiodegradable, landfilling causes vast environmental problems, and therefore, waste polymer energy recovery techniques are of great importance. Pyrolysis has advantages as all mixed plastics can be reduced back to petrochemicals. Fluidized beds have useful characteristics for energy recovery. They have an economic advantage in industrial operations due to low maintenance costs when compared to other reactors. Fluidizing beds provide flexibility in the operation that makes it possible to use various fluidizing agents and process conditions. Fluidizing beds were identified to be the best reactors for catalytic plastic pyrolysis as they provide large contact surface for the reaction to happen. The fluidizing beds have some limitations; the bed particles can erode the walls of the vessels, and the beds are sensitive to fibers, high amounts of metals, and fillers. Long-term stable operation of the fluidized bed can worsen the quality of the fluidization, and some operation conditions may cause defluidization. The paper reviewed the use of fluidization for energy recovery, and discussed its advantages and limitations. The fluidizing beds are promising reactors for energy recovery due to the flexibility of the operation. However, further investigation is required to understand and improve the quality of fluidization, ways to avoid defluidization, and parameters affecting the performance of the fluidised beds for energy recovery.
Keywords: Pyrolysis; Catalysts; Fluidized beds; Energy; Polymers